Nitrous Oxide Toxicity with Methylenetetrahydrofolate Reductase Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The neurological deterioration and death of a child with methylenetetrahydrofolate reductase (MTHFR) deficiency following anesthetization with nitrous oxide are reported from the University of Wisconsin Medical School, Madison, WI, and McGill University, Montreal.